Strength and pitfalls of the point of care testing: the central role of the laboratories for a successful goal - Buonocore, Ruggero; Sammartano, Antonino; Testa, Giulia; Giafusti, Delia; Ippolito, Luigi; Di Stasi, Bruna Brigida Carmela (Acta Biomedica Atenei Parmensis, 2024)
Point-of-care testing (POCT) is a well-known technology, which ensures fast results close to patient bed site. For this reason, POCTs accelerate the clinical decisions and could ameliorate the patient outcome. Nowadays POCT technology has been improved by providing portable and easy-to-use devices for the quantitative determination of clinical chemistry analytes, coagulation, and cardiac biomarkers (e.g., high sensitivity troponin assays). The advantages of POCT have improved the analysis time associated with delays due to transport in the laboratory thanks to the prompt execution of tests close to the patient and responding to the needs in emergency departments. Many POCT ensure a lead time in less than 15 minutes for a complete panel of clinical chemistry including electrolytes, ALT, AST, amylase, total bilirubin, calcium, albumin, creatinine, C-reactive protein (CRP) and glucose. An important effort has been made to develop POCT devices for Acute Myocardial Infarction (AMI) diagnosis. Considering cardiac injury biomarkers, in 2020 the European Society of Cardiology (ESC) coined the fourth definition of Acute Myocardial Infarction (AMI) defined as a clinical setting in presence of cardio-myocyte necrosis with acute myocardial ischemia. The opportunity to use POCT technologies for a quick and high sensitivity measurements represents a fundamental improvement for AMI differentiated diagnosis in critical conditions. In fact, to make the diagnosis of AMI is required a combination of criteria between the use of high sensitivity cardiac troponin I or T (hs-TnI and hs-TnT) with at least one value above the 99th percentile of the higher reference limit (1). In 2021 Apple et al. validated the test for hs-TnI using the Atellica VTLi hs-cTnI immunoassay, with a TAT of 8 minutes (2), Atellica POCT requires few drops of capillary blood or lithium heparin whole blood, meeting the criteria reported by ESC for AMI diagnosis. Apple et al. reported for Atellica VTLi hs-cTnI immunoassay an imprecision at the cardiac troponin (cTn) concentration of the lowest sex specific 99th percentile upper reference limit ≤ 10% CV and the measured hs-cTn concentrations in ≥50% of healthy males and females, which exceeds the assay limit of detection (LoD) (3). Nowadays POCT can be link with the most adopted laboratory information system (LIS). Besides to ensure an automatic flow of the results without manual transcription of data, it permits the opportunity to have a laboratory remote control on all the analytical platform deployed also far from the hubs and to storage all the results from patients to guarantee its traceability during the time. Although different point of strength, some consideration must consider when POCT are available in our hospitals. Quality specifications for POCT testing should be the same as those for centralized laboratories. In particular, the advantages of sensitive assays of cTns in allowing early diagnosis and prompt treatment cannot be side-stepped by using POCT methods with a low analytical sensitivity. Lacking harmonization and traceability, this issues force to consider POCT results very carefully. Indeed, in many cases POCT use a biological matrix that is not the common one used on automated laboratory analysers (ALA), giving hardly comparable results. For instance, Piccolo Express® AmLyte 13 required lithium heparin whole blood instead of serum, referring to different reference intervals. Moreover, ALT and AST methods present on Piccolo Express® AmLyte13 do not include P-5’-P as recommended by the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) for transaminase determination. Regarding hs-Tn the importance of the matrix is once more pivotal. Regarding cardiac biomarkers, the comparability between POCT hs-TnI and hs-TnI obtained with a laboratory automated immunoassay must evaluate before allowing the use of POCT results, since most laboratory in Italy use lithium heparin plasma or serum with the possibility of not comparable results. The traceability of hs-TnI methods is still lacking, thus every laboratory must validate its 99th percentile to established is own cut-off for AMI rule out. Hs-TnI POCT could be present in emergency department and could be employ for 0/1-hour protocol to exclude AMI, but how about the follow up determinations? If the first determination has been performed with POCT, is the result comparable with the central laboratory one? It is very important to know if these two analytical platforms are harmonized to guarantee the opportunity to established serial measurements as in case of evaluation of the degree of myocardial damage. Serial troponin measurement after AMI diagnosis is also important as a prognostic value for the evaluation of the reserve ejection fraction presented by the patient. Therefore, is pivotal for every laboratory to know the eventually bias between POCT and central laboratory instrumentation to decide whether it is acceptable or not, giving accurate instruction to the physician for a correct interpretation. Central laboratory instruments must check before starting the routine analysis, respecting the imprecision and bias declared by the producers. Moreover, as we know, external proficiency tests are mandatory for public clinical laboratory in Italy. Regarding POCT, ISO22870 lists specific requirements for the quality and competence of point-of-care testing (POCT) which are intended for medical laboratories in conjunction with ISO15189. Rampoldi et al. highlighted once more that clinical governance, connectivity, the role of the laboratory director and staff, quality control (QC), education, risk management and the role of the in vitro diagnostic companies are extremely crucial for the correct use and implementation of POCT (4, 5). In many cases POCT include an internal quality control provided by the producer with a known low and high concentrations of analytes intended to measure. The use of a third-party quality control is strongly advice exactly as for central laboratory instrumentation. In 2022 Emilia Romagna region (Italy) published a document giving indications for the laboratories working on its territory to harmonize the installation and application of these platforms (5, 6). Our concerning is high when we are informed that POCT could be available in future in private clinics without a connectivity to a laboratory. As POCT are user friendly, they could be also “error friendly” especially if the QC protocols and so the performances are not verified. POCT should not let to perform the test when even just one QC level is failed. Finally, the strength of POCTs is represented by their usefulness in emergency contexts, to guarantee timely clinical choices for better patient managing. Once more the network between the central laboratory and the POCT is necessary to achieve quality standards, so it is mandatory for the POCTs to be integrated with the central laboratory thanks to the support of connectivity. New clinical governance framework may be based on an integrated diagnostic structure, where POCT and central laboratory data are fully combined with all patient data to allow not only traditional policy, programme of quality assurance, risk management and technology assessment but also integrated for shared the patient management. Considering these issues, the role of laboratory is pivotal as a governance of POCT technologies used inside or outside the hospitals. Good procedures shared with emergency departments, a strict supervising of quality control and continuous training of users are the way to pursuit if we want to permit an accurate use and interpretation of results in clinical practice.